Les transferts de biens et les paiements de soutien entre concubins : une analyse des dispositions fiscales - Lareau, André (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1983)
Until recently, the Income Tax Act and its provincial counterpart had refused the common law spouses the tax treatment granted to « legal » spouses. Modifications were introduced in two specific areas of the act allowing these « outlaws » firstly a tax-free rollover when properties are transferred between them and secondly a deduction for the payor and a correlative inclusion for the beneficiary when an allowance is paid after the termination of the common law relationship. An analysis of these provisions indicate clearly that the effective scope of the changes will be of limited application since only « de facto » spouses from Ontario will be able to take advantage of them.